Abscopal effect: from a rare phenomenon to a new frontier in cancer therapy - Xueying Wang; Haoyu Zhang; XinZhang; Yong Liu (BMC, 2024)
Abstract Radiotherapy (RT) controls local lesions, meantime it has the capability to induce systemic response to inhibit distant, metastatic, non-radiated tumors, which is referred to as the "abscopal effect". It is widely recognized that radiotherapy can stimulate systemic immune response. This provides a compelling theoretical basis for the combination of immune therapy combined with radiotherapy(iRT). Indeed, this phenomenon has also been observed in clinical treatment, bringing significant clinical benefits to patients, and a series of basic studies are underway to amplify this effect. However, the molecular mechanisms of immune response induced by RT, determination of the optimal treatment regimen for iRT, and how to amplify the abscopal effect. In order to amplify and utilize this effect in clinical management, these key issues require to be well addressed; In this review, we comprehensively summarize the growing consensus and emphasize the emerging limitations of enhancing the abscopal effect with radiotherapy or immunotherapy. Finally, we discuss the prospects and barriers to the current clinical translational applications.